A complete Holocene climate and environment record for the Western Carpathians (Slovakia) derived from a tufa deposit. (March 2019) - Dabkowski, Julie; Frodlová, Jitka; Hájek, Michal; Hájková, Petra; Petr, Libor; Fiorillo, Denis; Dudová, Lydie; Horsák, Michal
Calcareous tufas are great archives of geochemical information for the reconstruction of past climate. Their importance increases in the regions where other proxies are rare, such as Western Carpathians. Here, we present the first whole-Holocene palaeoclimatic reconstruction for this region based on geochemical proxies. We analysed δ 18 O, δ 13 C and Mg/Ca ratio on tufa calcite of the Mituchovci site (White Carpathian Mountains, W Slovakia) and compared these with pollen, plant macrofossil and mollusc data. According to δ 18 O, two distinct thermal maxima occurred in the region, around 11.4 ka and between 7.3 and 6.9 ka BP. According to δ 13 C and Mg/Ca ratio, a steep increase in moisture and rainfall took place around 8.5 ka cal. BP, preceded by a cold and dry event. These events are well reflected in the biotic proxies and are suggested also by other palaeoenvironmental studies from the Carpathians. We found some later fluctuations, with dry and warm Bronze Age (ca. 3.6 ka cal. BP), cold and wet Urnfield period (ca. 2.8 ka cal. BP), warm Roman period (ca. 2 ka cal. BP) and cold but humid Migration period (ca. 1.5 ka cal. BP). We observed extreme abruptness and amplitude of the variation in all geochemical proxies in the last 500 years, when biotic proxies imply a very intense human deforestation. Land-use changes may have altered both the temperature regime in the studied fen and the carbon cycle in the recharge area.